Four-Color Alternating-Laser Excitation Single-Molecule Fluorescence Spectroscopy for Next-Generation Biodetection Assays - Yim, Seok W. (Clin Chem, 2012)
BACKGROUND: Single-molecule detection (SMD) technologies are well suited for clinical diagnostic applications by offering the prospect of minimizing precious patient sample requirements while maximizing clinical information content. Not yet available, however, is a universal SMD-based platform technology that permits multiplexed detection of both nucleic acid and protein targets and that is suitable for automation and integration into the clinical laboratory work flow. METHODS: We have used a sensitive, specific, quantitative, and cost-effective homogeneous SMD method that has high single-well multiplexing potential and uses alternating-laser excitation (ALEX) fluorescenceaided molecule sorting extended to 4 colors (4c-ALEX). Recognition molecules are tagged with different-color fluorescence dyes, and coincident confocal detection of ≥2 colors constitutes a positive target-detection event. The virtual exclusion of the majority of sources of background noise eliminates washing steps. Sorting molecules with multidimensional probe stoichiometries (S) and single-molecule fluorescence resonance energy transfer efficiencies (E) allows differentiation of numerous targets simultaneously. RESULTS: We show detection, differentiation, and quantification—in a single well—of (a) 25 different fluorescently labeled DNAs; (b) 8 bacterial genetic markers, including 3 antibiotic drug–resistance determinants found in 11 septicemia-causing Staphylococcus and Enterococcus strains; and (c) 6 tumor markers present in blood. CONCLUSIONS: The results demonstrate assay utility for clinical molecular diagnostic applications by means of multiplexed detection of nucleic acids and proteins and suggest potential uses for early diagnosis of cancer and infectious and other diseases, as well as for personalized medicine. Future integration of additional technology components to minimize preanalytical sample manipulation while maximizing throughput should allow development of a user-friendly (“sample in, answer out”) point-of-care platform for next-generation medical diagnostic tests that offer considerable savings in costs and patient sample.